Unveiling the central parsec region of an AGN: the Circinus nucleus in the near infrared with the VLT - Prieto, M; Meisenheimer, K; Marco, O; Reunanen, J; Contini, M; Clenet, Y; Davies, R; Gratadour, D; Henning, T; Klaas, U; Kotilainen, J; Leinert, C; et al. (2004)
VLT J- to M\p-band adaptive optics observations of the Circinus Galaxy on parsec scales resolve a central bright Ks-band source with a FWHM size of 1.9 $±$ 0.6 pc. This source is only visible at wavelengths longward of 1.6 $μ$m and coincides in position with the peak of the [Si VII]~2.48 $μ$m coronal line emission. With respect to the peak of the central optical emission, the source is shifted by $\sim$ 0.15\arcsec (2.8 pc) to the south-east. Indeed, it defines the vertex of a fairly collimated beam which extends for $\sim$ 10 pc, and which is seen in both continuum light shortward of 1.6 $μ$m and in H$α$ line emission. The source also lies at the center of a $\sim$ 19 pc size [Si VII] ionization {\it bicone}. Identifying this source as the nucleus of Circinus, its size is compatible with a putative parsec-scale torus. Its spectral energy distribution, characterized by a prominent narrow peak, is compatible with a dust temperature of 300 K. Hotter dust within a 1 pc radius of the center is not detected. The AGN luminosity required to heat this dust is in the range of X-ray luminosities that have been measured toward the central source. This in turn supports the existence of highly obscuring material, with column densities of $10^{24}$ cm$^{-2}$, that must be located within 1 pc of the core.